Posthuman Scale. Issue 1 (April 2016) - Thomsen, Mads Rosendahl
Abstract : Visions of the posthuman are almost inevitably tied up with questions of scale. The size of Frankenstein's creation sets him apart from humanity, the longevity of Virginia Woolf's Orlando makes her / him uncannily posthuman, and the travels of Gulliver constantly confront the protagonist with the issue of physical scale. This article investigates different dimensions of posthuman scale with examples from fiction, film, and transhumanist writings. From the sizes of bodies and the length of lives to the more complex matters of the scale of consciousness and the magnitude of social connections, what happens when an element of human existence is changed and becomes either very large or very small is a recurrent and important question. Such changes have consequences for ethical dispositions towards the lives of others, for the aesthetic appreciation or dislike of new beings, and for the ability to envision completely new ways of connecting to the world and others, for example through a cloud of shared thoughts, as Olaf Stapledon imagined. One special case of posthuman scale is the replication of the individual and the number of possible lives an individual can live without losing individuality, a question that is also pivotal for the idea of the human as a simulation that has been proposed by writers, filmmakers, and futurists alike.